Dietary and ergogenic supplementation to improve elite swimming players` performance and recovery - Wang, X.; Wang, H.; Wu, H. (Science & Sports, 2023)
Context Dietary supplements in sports are becoming increasingly popular. The strategic and cautious use of a few supplements and sports foods, preferably in cooperation with a sports nutrition specialist, may be beneficial to certain athletes in certain circumstances.